THE EFFECTIVENESS OF MEDIATION IN COMPLETING DIVORCE CASES IN JAMBI PROVINCIAL RELIGIOUS COURT - Fitriyah Alkaff; A. Husein Ritonga; A. A. Miftah Miftah (Yayasan Literasi Kita Indonesia, 2021)
The accumulation of cases always increases from year to year. For this reason, the Supreme Court issued Supreme Court Regulation (Perma) No.1 of 2016 concerning mediation procedures in court, as an effort to reduce the number of cases that go to court, including divorce. but unfortunately mediation does not show the expected success rate in religious courts. This research reveals the failure and success factors of mediation in the Jambi religious court, the role of the mediator in resolving divorce cases and exploring the effectiveness of mediation in divorce cases. This research is located at the location of divorce cases, namely the Jambi City Religious Court, the Kuala Tungkal Religious Court and the Sarolangun Religious Court. The results of this study prove that; first, the mediation success rate is only 4%. The failure factor for mediation is the lack of judges as mediators, there is no incentive funds for mediators who succeed in reconciling the mediator who does not have sufficient skills in dealing with the parties. Second, the role of the mediator in resolving divorce cases is not only as a facilitator but as a catalyst, educator, supporter and psychiatrist depending on the case at hand.